The marginalization of poetry : language writing and literary history - Perelman, Bob. (Princeton, N.J. : Princeton University Press, 1996)
Language writing, the most controversial avant-garde movement in contemporary American poetry, appeals strongly to writers and theorists interested in the politics of postmodernism and in iconoclastic poetic form. Drawing on materials from popular culture, avoiding the standard stylistic indications of poetic lyricism, and using nonsequential sentences are some of the ways in which language writers make poetry a more open and participatory process for the readers. Reading this kind of writing, however, may not come easily in a culture where poetry is treated as property of a special class. It is this barrier that Bob Perelman seeks to break down in this fascinating and comprehensive account of the language-writing movement. A leading language writer himself, Perelman offers insights into the history of the movement and discusses the political and theoretical implications of the writing - including postmodern fragmentation, the poetics of avant-garde formations, the politics of multicultural poetics, and gender and the avant-garde. He provides detailed readings of work by Lyn Hejinian, Ron Silliman, and Charles Bernstein, among many others, and compares it to a wide range of other contemporary and modern American poetry.
1. The marginalization of poetry -- 2. Language writing and literary history -- 3. Here and now on paper: the avant-garde particulars of Robert Grenier -- 4. Parataxis and narrative: the new sentence in theory and practice -- 5. Write the power: orthography and community -- 6. Building a more powerful vocabulary: Bruce Andrews and the World (Trade Center) -- 7. This page is my page, this page is your page: gender and mapping -- 8. An alphabet of literary history -- 9. A false account of talking with Frank O'Hara and Roland Barthes in Philadelphia.
Includes bibliographical references (pages 167-181) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Universidad Sergio Arboleda; American poetry -- 20th century -- History and criticism -- Theory, etc; Language and languages in literature; Poetics; Poésie américaine -- 20e siècle -- Histoire et critique -- Théorie, etc; Langage et langues dans la littérature.; Poétique.; 18.06 Anglo-American literature; LITERARY CRITICISM -- Poetry; Language and languages in literature; Poetics; Experimentelle Lyrik; Lyriktheorie; Moderne; USA; Amerikaans; Dichtkunst; American poetry -- 20th century -- History and criticism -- Theory, etc; Language and languages in literature; Poetics; Poésie américaine -- 20e siècle -- Histoire et critique -- Théorie, etc; Poétique.; 1900-1999; Geschichte 1970-1995.; American poetry -- 20th century -- History and criticism -- Theory, etc; American poetry -- History and criticism -- Theory, etc -- 20th century; Language and languages in literature; Poetics; Criticism, interpretation, etc